Spatio-temporal comparisons of the hydrogen-alpha line width and ALMA 3 mm brightness temperature in the weak solar network - Tarr, Lucas A.; Kobelski, Adam R.; Jaeggli, Sarah A.; Molnar, Momchil; Cauzzi, Gianna; Reardon, Kevin P. (Frontiers in Astronomy and Space Sciences, 2023)
Comparisons between the Atacama Large Millimeter/sub-millimeter Array (ALMA) 3mm emission and a range of optical and UV solar observations have found the strongest correspondence between the width of the hydrogen alpha line at 656.3nm and the 3mm brightness temperature. Previous studies on the oscillatory power of \pmode{}s using ALMA Band 3 and Band 6 data in the 3 to 5 minute period bandpass have found a confusing mix of results, with many reporting a complete lack of the \pmode{} enhancement typically found in other chromospheric observables. We study these issues using an extensive, publicly available coordinated data set targeting a region of weak network flux near disk center at time SOL2017-03-17T15:42-16:45. We focus on the Interferometric Bidimensional Spectropolarimeter (IBIS) H-alpha and ALMA 3mm data series. We confirm the strong correlation between the H-alpha line width and the 3mm brightness temperature, but find a bimodal relation between the two diagnostics, with a shallower slope of 7.4e-5Å/K in cooler regions and steeper slope of 1.2e-4Å/K in hotter regions. The origin of the bimodal distribution is unknown, but does hold for the duration of the observations. Both slopes are steeper than a previously reported value, but this is likely due to systematic differences in the analysis. We then calculate the oscillatory power in the H-alpha and 3mm data. The IBIS data clearly show the \pmode{} oscillations in spatially averaged power spectra while the ALMA data do not. However, when we remove IBIS data at times corresponding to the ALMA calibration windows, the spatially averaged power spectra for the two data series are nearly identical, with a Pearson correlation coefficient of 0.9895. Further, the power in the two bands remains strongly correlated when the spatial information is retained but the power is integrated over different temporal frequency bands. We therefore argue that the lack of observed \pmode{}s in the ALMA data may be predominantly due to spectral windowing induced by the timing and duration of the calibration observations. Finally, we find that spatial maps of oscillatory power at 3mm display the pattern of magnetic shadows and halos typically displayed by other chromospheric diagnostics.